2017
DOI: 10.1093/jac/dkx264
|View full text |Cite
|
Sign up to set email alerts
|

Covert dissemination of carbapenemase-producing Klebsiella pneumoniae (KPC) in a successfully controlled outbreak: long- and short-read whole-genome sequencing demonstrate multiple genetic modes of transmission

Abstract: BackgroundCarbapenemase-producing Enterobacteriaceae (CPE), including KPC-producing Klebsiella pneumoniae (KPC-Kpn), are an increasing threat to patient safety.ObjectivesTo use WGS to investigate the extent and complexity of carbapenemase gene dissemination in a controlled KPC outbreak.Materials and methodsEnterobacteriaceae with reduced ertapenem susceptibility recovered from rectal screening swabs/clinical samples, during a 3 month KPC outbreak (2013–14), were investigated for carbapenemase production, antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 38 publications
6
68
0
1
Order By: Relevance
“…While these data are subject to the biases of the underlying databases within which clinically relevant (MDR and virulence) plasmids are overrepresented, they are also consistent with the findings above regarding overall pan--genome diversity. These data imply that MDR clones frequently acquire and lose plasmids, consistent with the high plasmid diversity reported previously for ST258 52,53 and several others 7 , and with data from recent investigations of Kp circulating in hospitals which showed that individual plasmids transferred frequently between clones 54,55 . In contrast, the hypervirulent clones were associated with comparatively low plasmid diversity, mirrored by generally narrow plasmid load distributions.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…While these data are subject to the biases of the underlying databases within which clinically relevant (MDR and virulence) plasmids are overrepresented, they are also consistent with the findings above regarding overall pan--genome diversity. These data imply that MDR clones frequently acquire and lose plasmids, consistent with the high plasmid diversity reported previously for ST258 52,53 and several others 7 , and with data from recent investigations of Kp circulating in hospitals which showed that individual plasmids transferred frequently between clones 54,55 . In contrast, the hypervirulent clones were associated with comparatively low plasmid diversity, mirrored by generally narrow plasmid load distributions.…”
supporting
confidence: 91%
“…This is particularly worrying from a hospital infection control perspective since many of the MDR clones investigated here appear well adapted to transmission and colonisation in the human population, and are frequent causes of hospital outbreaks 7,8 . Given the mounting evidence that MDR clones can carry multiple plasmids at limited fitness cost [64][65][66] and frequently exchange plasmids with other bacteria 54,55 , it seems these MDR clones may also be the perfect hosts for consolidation and onwards dissemination of MDR and virulence determinants. The greatest concern is that these determinants will be consolidated onto a single mobile genetic element; indeed mosaic Kp plasmids carrying AMR genes plus iuc and rmpA2 have already been reported in an MDR Kp clone 30 , and Escherichia coli plasmids bearing iuc, rmpA and AMR genes have been detected in Kp 27 .…”
mentioning
confidence: 99%
“…This suggests K. pneumoniae receives DNA from a wider diversity of HGT partners; indeed lowest common ancestor analysis of K. pneumoniae accessory genes has implicated >20 distinct genera as DNA donors, including numerous other members of the Enterobacteriaceae but also diverse groups such as Acinetobacter, Burkholderia, Streptomyces, Vibrio, Xanthomonas and Xyella [9]. More direct evidence for K. pneumoniae engaging in inter--species HGT can be found in recent genomic comparisons of carbapenem--resistant Enterobacteriaciae in hospitals, which captured identical or highly similar carbapenemase encoding plasmids and/or transposons from K. pneumoniae and other species originating from the same ward and/or patient (E. coli, E. cloacae, Enterobacter asburiae, Citrobacter freundii, Klebsiella oxytoca, Raoultella ornothinolytica) [73][74][75].…”
Section: Ecological Rangementioning
confidence: 99%
“…SNVs with which to identify lineages and AMR genes, bolstered by long-read sequencing to resolve plasmids and AMR gene context and to maximize resolution for detecting transmission. While this strategy has been used in other studies [30][31][32][33] , ours is the first to adopt multiplex nanopore sequencing and hybrid assembly to rapidly and cost-efficiently complete genome sequences of interest in a high-throughput manner [11,12] (Tables S3, S4).…”
Section: This Study Employed Illumina Short-read Wgs To Identify Highmentioning
confidence: 99%